2020
DOI: 10.1167/iovs.61.11.38
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Investigation of Retinal Function in Patients with Achromatopsia

Abstract: To investigate the long-term natural history of retinal function of achromatopsia (ACHM). METHODS. Subjects with molecularly confirmed ACHM were recruited in a prospective cohort study of mesopic microperimetry. Coefficient of repeatability and intraclass correlation coefficient (ICC) of mean sensitivity (MS) were calculated. Best-corrected visual acuity (BCVA), bivariate contour ellipse area (BCEA), contrast sensitivity (CS), MS, total volume (V TOT), and central field volume (V 5°) from volumetric and topogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 48 publications
6
29
1
Order By: Relevance
“…Our findings are in agreement with the observations of Sundram et al who reported a decline of MS with age in 40 patients [23]. Conversely, Aboshiha et al and more recently Georgiou et al did not observe significant changes in MS in 38 and 18 patients, respectively [9,24]. These discrepancies may be due to the shorter follow-up reported in the first case (i.e., 19.5 months) [9] and to the different distribution of mutated genes [24].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are in agreement with the observations of Sundram et al who reported a decline of MS with age in 40 patients [23]. Conversely, Aboshiha et al and more recently Georgiou et al did not observe significant changes in MS in 38 and 18 patients, respectively [9,24]. These discrepancies may be due to the shorter follow-up reported in the first case (i.e., 19.5 months) [9] and to the different distribution of mutated genes [24].…”
Section: Discussionsupporting
confidence: 93%
“…As regards the retinal function, we found that MS negatively correlated with patient's age and decreased significantly over the follow-up period. To date, only few studies assessed the MS of ACHM patients by MP [9,23,24,32]. Our findings are in agreement with the observations of Sundram et al who reported a decline of MS with age in 40 patients [23].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Several studies explored the clinical course of ACHM patients to assess disease progression [18,19,22,[25][26][27][28]. Although some reports showed visual and structural deterioration [18,19,22,28,29], other studies report no correlation of clinical presentation with age [12,17,25].…”
Section: Introductionmentioning
confidence: 99%